Content development and management processes of ICT initiatives in Indian agriculture - Glendenning, C.J.; Ficarelli, P.P. (SAGE Publications, 2011)
In the last decade, many ICT projects in Indian agriculture have emerged, which either substitute or support extension services by enabling farmers' access to information. Information that is context specific to farmers' local situations can have important farm outcomes. The localization of content is influenced by how the ICT projects access, assess and deliver content. This paper develops a content development and management process framework, which is applied to six well-known ICT projects in Indian agriculture. Despite differences in scale, mechanisms of delivery and the extent of content localization, all projects use a network of experts in relevant fields to provide content. Yet, their collective knowledge cannot be tapped easily across the different platforms. To mainstream such ICT efforts and knowledge management in agriculture for rural livelihoods, a centralized search engine to access the dispersed agricultural information and network of experts is thus suggested.